The roots of ill-governance and corruption - Santhakumar, V. (SAGE, 2014)
This book provides a comprehensive assessment of the motivation behind corruption and ill-governance in countries, such as India. It presents a sound theoretical structure outlining the journey through various phases of elitism, counter-elitism, competitive populism, and, finally, good governance. The political willingness to bring in good governance, the book argues, depends on the electoral importance of the middle classes. Ironically, however, such a middle class emerges out of the policies of distributing private goods, including education, facilitated through counter-elite capture and comp.